Cadmium toxicity investigated at the physiological and biophysical levels under environmentally relevant conditions using the aquatic model plant Ceratophyllum demersum. Issue 4 (3rd February 2016) - Andresen, Elisa; Kappel, Sophie; Stärk, Hans‐Joachim; Riegger, Ulrike; Borovec, Jakub; Mattusch, Jürgen; Heinz, Andrea; Schmelzer, Christian E. H.; Matoušková, Šárka; Dickinson, Bryan; Küpper, Hendrik
Summary: Cadmium (Cd) is an important environmental pollutant and is poisonous to most organisms. We aimed to unravel the mechanisms of Cd toxicity in the model water plant Ceratophyllum demersum exposed to low (nM) concentrations of Cd as are present in nature. Experiments were conducted under environmentally relevant conditions, including nature‐like light and temperature cycles, and a low biomass to water ratio. We measured chlorophyll (Chl) fluorescence kinetics, oxygen exchange, the concentrations of reactive oxygen species and pigments, metal binding to proteins, and the accumulation of starch and metals. The inhibition threshold concentration for most parameters was 20 nM. Below this concentration, hardly any stress symptoms were observed. The first site of inhibition was photosynthetic light reactions (the maximal quantum yield of photosystem II (PSII) reaction centre measured as F v / F m, light‐acclimated PSII activity ΦPSII, and total Chl). Trimers of the PSII light‐harvesting complexes (LHCIIs) decreased more than LHC monomers and detection of Cd in the monomers suggested replacement of magnesium (Mg) by Cd in the Chl molecules. As a consequence of dysfunctional photosynthesis and energy dissipation, reactive oxygen species (superoxide and hydrogen peroxide) appeared. Cadmium had negative effects on macrophytes at much lower concentrations than reported previously, emphasizing the importance of studies applying environmentally relevant conditions. A chain of inhibition events could be established.